Unusual etiology of stroke in young adults: think of Takayasu’s arteritis - Aglave, Vikram; Nagendra, Shashank; Ojha, Pawan T.; Jagiasi, Kamlesh A.; Kharat, Sumit; Barvalia, Prachi; Gaikwad, Abhijit (International Journal of Advances in Medicine, 2021)
Takayasu arteritis is an uncommon inflammatory disease of vessels that preferentially affects the aorta and its major branches. It can be a potential cause of stroke in young adults. Current study included 7 patients aged between 18 to 48 years. Each patient had varying presentations of stroke with Takayasu’s arteritis along with other neurological symptoms. Four of the 7 patients presented with ischemic strokes, one with hemorrhagic stroke, one with TIAs and one with syncopal attacks. All the patients had elevated erythrocyte sedimentation rates. Five of the seven patients were treated with steroids and methotrexate. Two were treated with azathioprine and steroids. Antiplatelets were given for those patients who had strokes and TIAs. Our cases demonstrate that Takayasu arteritis can present with varying presentations including stroke. Thus, it is important to consider Takayasu’s arteritis as an unusual etiology of stroke especially in young adults.